The Application of Project Based Learning Model in the Implementation of the Merdeka Curriculum to Enhance Students' Concept Mastery in IPAS Learning - Weryanti Laen Langi’; Yohanis Padallingan; Marten Liling Parumbuan (Edumaspul: Jurnal Pendidikan, 2024)
The purpose of this research is to investigate the improvement of students' conceptual mastery in IPAS subjects through the implementation of the Project Based Learning (PjBL) model. This study is classified as a classroom action research with students from the fourth grade of SDN 5 Makale, totaling 29 students, as the subjects. Data analysis employs qualitative descriptive analysis. The research findings indicate that the implementation of the Project Based Learning (PjBL) model within the framework of the independent curriculum can enhance students' conceptual mastery. This is evident from the results of the students' conceptual mastery tests at the end of each cycle. The students' learning completeness in Cycle I was 51.72%, which increased to 86.20% in Cycle II.